2020
DOI: 10.3389/fpsyg.2020.02054
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being and Intrinsic Motivation: Relationship in Students Who Begin University Studies at the School of Education in Ciudad Real

Abstract: More and more studies and research have found a positive relationship between the participation of young peoplein altruistic activities and helping others. It is interesting to discover the relationship that personal and vocational satisfaction play in the preparation and training for the teaching profession. For students who begin university studies related to teaching, their psychological well-being and motivation toward this activity are very relevant aspects to consider. The access to and attainment of a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Academic motivation is a multivariate set of beliefs and behaviours, which are linked to students’ academic achievement and wellbeing, such as self-efficacy, self-regulation capability, learning engagement, perceived learning value, reasons for studying, achievement motives, goals, resilience and adaptability [ 12 ]. Research indicates the stronger a students’ academic motivation, the stronger the perception of their wellbeing is, and vice versa [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Academic motivation is a multivariate set of beliefs and behaviours, which are linked to students’ academic achievement and wellbeing, such as self-efficacy, self-regulation capability, learning engagement, perceived learning value, reasons for studying, achievement motives, goals, resilience and adaptability [ 12 ]. Research indicates the stronger a students’ academic motivation, the stronger the perception of their wellbeing is, and vice versa [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researches highlighted the negative impact of the COVID-19 pandemic on the psychological well-being of college students, who are likely to develop post-traumatic stress disorder, anxiety, depression, and other symptoms of distress [ 16 ]. A study conducted among students of a pedagogical university showed that there is a positive correlation between the perception of psychological well-being of participants and their academic motivation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Well-being is a complex structure related to optimal experience and functionality, and indicators of well-being should be positively related to the intrinsic motivations of individuals [54,55]. González Olivares and colleagues [56] analyzed the relative influence of the different intrinsic motivation factors on psychological well-being with a linear regression analysis. They found that interest/enjoyment, which correlates with intrinsic motivation, has the greatest influence on well-being, and all dimensions of well-being correlate positively with intrinsic motivation.…”
Section: Discussionmentioning
confidence: 99%